(3OQGSGJ aj EbJUGOjGJ GdRQGYI hGdJfejI GdQjajIs - (3QaYJ(B, (3dbhTIs ((3GdbGgQI(B:s (3GdecJHI GdCcGOjejI(B,s, 1993)
(3GdQjY GdRQGYj hGdEjLGQ GdQSej(B- (3GdbWGY GdRQGYj GdeUQj(B- (3JaJJ GdedcjI GdRQGYjI hGdONd GdRQGYj(B- (3SYQ GdYQV GdRQGYj(B-(3Jahb eYOd GdJVNe aj GdQja Ydi eYOd GdJVNe aj GdMVQ(B- (3GdSjGSI GdMchejI aj eLGd GdbeM(B- (3GdJfejI(B- (3GdecjfI GdRQGYjI hGdJfejI(B- (3GdYed GdRQGYj GdegGLQ(B- (3GdEfOeGL GdEUWfGYj Hjf GdbQjI hGdeOjfI(B.s
Keywords: (3EbJUGOjGJ GdRQGYIs; (3GdJfejI GdQjajIs; (3GdRQGYIs